Spirulina Platensis as Biocoagulant to Reduce Turbidity and Total Suspended Solids in Domestic Wastewater - Fathiya Nur Afifah; Fayza Nur Rachmalia; Frista Ananda Rizky; Hasna Khairunnisa; Nida Ulhaq Filardhiani; Lia Kusumaningrum (Universitas Diponegoro, 2024)
It is essential to treat wastewater before it is discharged into water bodies. The wastewater treatment method that is widely used is coagulation using the synthetic coagulant PAC, whose continuous use can harm human health and reduce the pH value of the water. Therefore, wastewater treatment innovation is needed to overcome this problem. This study will examine the potential of Spirulina platensis as a biocoagulant to reduce turbidity and TSS. This research was conducted in 3 stages, starting from the extraction, protein test, and optimum dose test. The results showed that Spirulina platensis has 0.0114375% protein in 20 gr and can reduce the lowest turbidity at doses of 10-5 ml / L and 10-10 ml / L (in 2 injections) with an effectiveness value of reducing turbidity levels by 63.02% and able to reduce the lowest TSS levels at doses 10-10 ml / L (in 2 injections ) with an effectiveness value of reducing levels by 85%. Based on the Wilcoxon test, it was found that the P-value < 0.05, which means that there is a significant difference in TSS values and turbidity between the results before and after Spirulina platensis biocoagulant treatment.